Characterization and discovery of miRNA and miRNA targets from apomictic and sexual genotypes of Eragrostis curvula - Garbus, Ingrid (2019)
Weeping lovegrass (Eragrostis curvula [Shrad.] Nees) is a perennial grass found in semi-arid regions that is well adapted for growth in sandy soils and drought conditions. E. curvula constitutes a polymorphic complex that includes cytotypes with different ploidy levels (from 2x to 8x), where most polyploids are facultative apomicts, although both sexual reproduction and full apomixis have been reported in this species. Apomixis is thought to be associated with silencing of the sexual pathway, which would involve epigenetic mechanisms. However, a correlation between small RNAs and apomixis has not yet been conclusively established. Aiming to contribute to the elucidation of their role in the expression of apomixis, we constructed small RNA libraries from sexual and apomictic E.curvula genotypes via Illumina technology, characterized the small RNA populations, and conducted differential expression analysis by comparing these small RNAs with the E. curvula reference transcriptome. We found that the expression of two genes is repressed in the sexual genotype, which is associated with specific microRNA expression. Our results support the hypothesis that in E. curvula the expression of apomixis leads to sexual repression.